2013
DOI: 10.3892/ijo.2013.1946
|View full text |Cite
|
Sign up to set email alerts
|

Genistein induces G2/M cell cycle arrest and apoptosis via ATM/p53-dependent pathway in human colon cancer cells

Abstract: Soybean isoflavones have been used as a potential preventive agent in anticancer research for many years. Genistein is one of the most active flavonoids in soybeans. Accumulating evidence suggests that genistein alters a variety of biological processes in estrogen-related malignancies, such as breast and prostate cancers. However, the molecular mechanism of genistein in the prevention of human colon cancer remains unclear. Here we attempted to elucidate the anticarcinogenic mechanism of genistein in human colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 38 publications
8
95
0
1
Order By: Relevance
“…Guo et al [48] have shown that dietary NiCl 2 can cause G2/M phase cell-cycle arrest in kidneys of broiler via ATM-Chk1/Chk2 pathways. Zhang et al [49] have reported that genistein can induce G2/M cell-cycle arrest via the ATM/p53-dependent pathway in human colon cancer cells. It has been found also that mangiferin can induce cell-cycle arrest at the G2/M phase through the ATR-Chk1 pathway in HL-60 leukemia cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [48] have shown that dietary NiCl 2 can cause G2/M phase cell-cycle arrest in kidneys of broiler via ATM-Chk1/Chk2 pathways. Zhang et al [49] have reported that genistein can induce G2/M cell-cycle arrest via the ATM/p53-dependent pathway in human colon cancer cells. It has been found also that mangiferin can induce cell-cycle arrest at the G2/M phase through the ATR-Chk1 pathway in HL-60 leukemia cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cdc2 activation depends on the dephosphorylation of Tyr15 by cdc25c. Otherwise, p53 and the p53-responsive gene, p21, can suppress cyclin B1 and cdc2 expression by inhibiting either cdc2 kinase activity or blocking the interaction of cyclin B1-cdc2 complexes with their substrates, leading to G2/M-phase cell cycle arrest (23)(24)(25)(26)(27). Furthermore, the MEK-ERK pathway has crosstalk with p53/p21, and Bax is a key target of the p53 transcription process in aspects of cell apoptosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have demonstrated that flavonoids inhibit cell growth by inducing S phase cell cycle arrest in prostate cancer cells (19)(20)(21). Flavonoids have also been documented to arrest cell-cycle progression at G0/G1 and G2/M in prostate cancer cells (22)(23)(24). These results indicate that flavonoids may block cell growth at multiple stages of the cell cycle (25).…”
Section: Discussionmentioning
confidence: 53%